Efektifitas Pendidikan Kesehatan Tanda Bahaya Kehamilan Terhadap Kepatuhan Antenatal Care Di Masa Covid-19 - Riance Mardiana Ujung (Publikasi Indonesia, 2022)
Every pregnancy carries risks for the mother. Early detection of danger signs and symptoms during pregnancy is the best effort to prevent serious disruption to pregnancy or the safety of pregnant women. During this Covid-19 pandemic, to get health services, you must maintain health protocols such as wearing masks, washing hands, and maintaining a minimum distance of 1 meter. The survey results found K1 in 2020 as many as 258 people (74.1%) and K4 as many as 198 people (57%). There are 24 pregnant women with high risk with causes including Chronic Energy Deficiency (KEK), grande multi gravida, pregnancy interval of less than 1 year, age at risk, hepatitis, HIV and Post SC. This study aims to see the effectiveness of providing health education about the danger signs of pregnancy on Antenatal Care Compliance during the Covid-19 Period. This type of research is an action research type of pre-experimental one-group pre-post test design, by means of a group before being given a pre-test and after a post-test. The population and sample were all pregnant women in the working area of ??the Siatas Barita Health Center who were present at the time of the implementation of the pregnant women class totaling 41 people. Test the validity of the instrument using the Corrected Item-Total Correlation of each question item. Reliability test using Croanbach's Alpha value. Methods Data analysis is the univariate method to get an overview of the frequency distribution of respondents from each variable. Bivariate analysis was carried out to test whether there was an effect of each independent variable with the dependent variable using Wilcoxon test statistics and the results were narrated. Based on the results of the questionnaire from 41 respondents, a pre-test was carried out as much as 29.3% had less knowledge and 70.7% had good knowledge. After the post test, there was an increase in knowledge of pregnant women even though there were still some who were lacking, namely 14.6% and 85.4% had good knowledge. In the table of results for the normality test, it shows that the value of sig. Pre test > 0.05, namely p = 0.062 and the value of sig. Post test > 0.05, namely p = 0.071, so it can be concluded that the results of the normality test of the pre-test and post-test of the research sample are normally distributed and can be continued with a different test using paired t-test with pre-test results of 21.00 ± 5.394 and posttest 23 ,05 ± 4,593. This means that there is an increase in respondents' knowledge about health education about pregnancy danger signs. Furthermore, based on the significance value (p-value) of 0.009 (<0.05). Based on the results of statistical tests, the treatment of health education about the danger signs of pregnancy has a significant influence on the knowledge of pregnant women about antenatal care compliance in pregnant women during the covid-19 period.